DEVELOPMENT OF POLYA’S TECHNIQUE-BASED VIDEO TUTORIALS FOR STUDENTS’ PROCEDURAL FLUENCY IN COLLEGE ALGEBRA - Joel C. Patiño Jr (Utilitas Mathematica, 2025)
This study aimed to develop Polya's video tutorials for improving students’ procedural fluency in college algebra. The four concepts of problem-solving introduced by George Polya, namely understanding the problem, devising a plan, carrying out the plan and looking back, form the foundation of the video tutorials. The first semester of the academic year 2023–2024 was the covered time of the study with one hundred College of Teacher Education students majoring in mathematics at Cotabato State University as respondents. Descriptive research design using a survey method was utilized. Based on the results, the majority of respondents believed Polya's technique-based video tutorials were very good in terms of layout, content, and usefulness. The video's layout or design is suitable for learners, and the video's engaging content places a strong emphasis on the four problem-solving principles. Additionally, video tutorials are unquestionably crucial for learning mathematics because they provide an alternative source of information for efficient problem-solving. Personalized tutorials can be very beneficial for both instructional learning and self-learning to help students learn various mathematical problems.